Cost‐effectiveness of Micra™ VR leadless pacemaker in patients with bradycardia and atrial fibrillation in Australia - Koji Makino; Mia Mudge; Michelle Hill; Chelsea Zaunmayr; Dominic Tilden (Journal of Arrhythmia)
Abstract Background Micra™ VR Transcatheter Pacing System (Micra VR) is a single‐chamber transcatheter leadless pacemaker. Absence of leads and subcutaneous pocket reduces or completely eliminates the risk of complications associated with the conventional transvenous pacemakers (TVPM). When compared with TVPM, the leadless technology provides a quicker postimplantation recovery and causes less cosmetic concerns/discomfort providing better patient experiences in the long run. We performed a modeled cost‐utility analysis of Micra VR versus TVPM for the management of patients with bradycardia. Methods We developed a Markov model comparing Micra VR to TVPM over the device battery life of 17 years. Key data inputs were drawn from the MICRA Coverage with Evidence Development (CED) study. Costs were obtained from Australian sources. The analysis is from the perspective of the Australian healthcare system. Results The risks of complications, including device‐related events, in real‐world clinical practice were relatively low for TVPM. The magnitude of cost savings arising from risk reductions provided by Micra VR was however sizable, offsetting roughly a quarter of its additional device cost. Over the 17‐year model period, Micra VR was associated with an estimated incremental cost of A$4277 and an incremental quality‐adjusted life years (QALYs) of 0.09 when compared with TVPM, yielding an incremental cost‐effectiveness ratio of A$47 379 per QALY gain. Conclusions Micra VR is likely to offer a cost‐effective alternative to the conventional TVPM technology for the management of patients with bradycardia.